Gambaran Sarana dan Prasarana Bimbingan dan Konseling di Sekolah SMP Swasta Cerdas Murni - Daulay, Nurussakinah; Asy Ary Rambe, Afghan Bai; Abdillah, Fahmil; Hidayat, Dodi; Syafira Dewi, Nabila Atari; Aritonang, Padila Sari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study has the objective of describing the condition of guidance and counseling facilities and infrastructure at the Smart Pure Private Middle School, Deli Serdang Regency, North Sumatra. This study used qualitative research methods. The research subject was the Smart Pure private junior high school (SMP). Data collection instruments were in the form of observations and also interviews about the condition of guidance and counseling facilities and infrastructure at the Smart Pure Private Middle School. Data analysis techniques in this study used descriptive data analysis. The results of the study show that the availability of guidance and counseling rooms is quite adequate, the availability of special counseling rooms and also the inhibiting factors for the availability of counseling guidance facilities Keywords: facilities, infrastructure, counseling guidanc